(untitled) (Journal of the College of Basic Education, 2024)
The paradox structure in AL Buraikan constitutes a fertile topic within the mechanisms of the reader’s horizon of expectation, and the reader also has a major role in understanding the poem, Ashe owns a a reserve thet qualifies him to receive a poetic text that Contains signs, structures, connotations, paradoxes, and other elements of the poetic structure. Inacomprehensive framework that shows its role in it and then its ability to create an aesthetic impact, because it is one of the ways to shock the recipient’s horizon of expectations’s horizon of expectations and part of building another horizon for reading.It modifies what is expected of it.And because of it, the tension distance required to integrate the recipient with the text is created, without a doubt, Thereis no doubt that AL Buraikan, his uniqueness and his attentions remain what determine on our focus one approach rather than another, and the text will inspire reading with evidence and reinforcement.